Climate change perceptions, knowledge and adaptation responses of smallholder, crop-livestock farmers in Mediterranean-type ecosystems: case studies from the Overberg District, South Africa - Dippenaar, Elsje Marthina (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScConsEcol)--Stellenbosch University, 2022.